Kesiapan Belajar Siswa di Kelas Kimia dengan Kurikulum Prototipe - Farwati, Ratna (Universitas Negeri Padang, 2022)
In 2022, the government offers three curriculum options to schools in Indonesia. The three curricula are the 2013 Curriculum, Kurikulum Darurat (Emergency Curriculum), and Prototype Curriculum. Students as subjects in learning must be ready with any curriculum used by their school. The Prototype Curriculum is new. Therefore, this study was conducted to determine students learning readiness in schools that implement the Prototype Curriculum. The research data was collected by surveying 98 students whom took chemistry class in one high school at Ogan Komering Ilir Regency, South Sumatra. The survey was conducted from April to May 2022. The survey data was collected using a questionnaire with 30 statements, on a scale of 1-5, consisting of components of physical, psychological, material, and cognitive readiness. This research instrument adopts what has been developed by Slameto (2013). The data is tabulated, calculated on the average per component of each student and all students, then calculated as the average of all data to categorize students learning readiness at the school. The average value of 1-2,5 means not ready, while the value of 2,6-5 means ready. The survey results showed that the average value of physical readiness was 4.33; psychic readiness was 4.00; material readiness was 4.20; and cognitive readiness was 3.23. Thus, students at one SMA in Ogan Komering Ilir Regency have good learning readiness in chemistry class with the Prototype Curriculum. Although the cognitive readiness of students is not optimal, teachers can improve it by designing integrative and fun learning such as the STEM learning model.